Challenges and Approaches to Green Social Prescribing During and in the Aftermath of COVID-19: A Qualitative Study - Fixsen, Alison; Barrett, Simon (Frontiers in Psychology, 2022)
The last decade has seen a surge of interest and investment in green social prescribing, however, both healthcare and social enterprise has been impacted by the COVID-19 crisis, along with restricted access to public green spaces. This study examines the challenges and opportunities of delivering green social prescribing during and in the aftermath of COVID-19, in the light of goals of green social prescribing to improve mental health outcomes and reduce health inequalities. Thirty-five one-to-one interviews were conducted between March 2020 and January 2022. Interviewees included Link Workers and other social prescribers, general practitioners (GPs), managers, researchers, and volunteers working in urban and rural Scotland and North East England. Interview transcripts were analyzed in stages, with an inductive approach to coding supported by NVivo. Findings revealed a complex social prescribing landscape, with schemes funded, structured, and delivered diversely. Stakeholders were in general agreement about the benefits of nature-based interventions, and GPs and volunteers pointed out numerous benefits to participating in schemes such as parkrun. Link Workers were more circumspect about suggesting outdoor activities, pointing out both psychological and practical obstacles, including health anxieties, mobility issues, and transport deficits. Exacerbated by the pandemic, there was a way to go before older and/multi-morbidity clients (their largest cohort) would feel comfortable and safe to socialize in open air spaces. Our findings support the premise that time spent in open green spaces can alleviate some of the negative mental health effects compounded by the pandemic. However, the creation of healthy environments is complex with population health intrinsically related to socioeconomic conditions. Social disadvantage, chronic ill health and health crises all limit easy access to green and blue spaces, while those in the most socially economically deprived areas receive the lowest quality of healthcare. Such health inequities need to be borne in mind in the planning of schemes and claims around the potential of future nature-based interventions to reduce health inequalities.